Preparation of Whey-Based Banana Beverage and its Quality Evaluation - Shrestha, Kunjal; Dahal, Abhishek (Himalayan Journal of Science and Technology, 2021)
A value-added functional beverage was formulated utilizing unprocessed whey with excellent nutritional qualities and bland flavors; along with banana juice and the required amount of sugar. Five different formulations were prepared with varying proportions of whey, banana juice, and sugar. Sensory analysis was carried out for all five formulations and based on statistical analysis the one which showed the highest value for body, color, flavor, taste, and overall acceptability was selected for further analysis (85% liquid whey and 15% banana juice). The shelf-life of the final product was observed for 30 days at room temperature (25±5°C) and refrigerated temperature (7±1ºC). A significant variation in body, color, flavor, taste, and overall acceptability were observed by varying the composition of whey and banana juice (p<0.05). The beverage was pasteurized at 82.5°C for 20 min and stored at normal (25±5°C) and refrigerated (7±1°C) for 30 days. The effects of storage time and temperature on physicochemical (TSS, pH, acidity) and microbial (TPC, yeast & mold count) properties were evaluated. Out of five formulations, the one selected via sensory analysis had TSS of 12.4°Bx, total solids 14.21%, 0.302% acidity, pH 5.72, 5.087% reducing sugar, 0.53% protein, 0.56% ash, 0.87% crude fiber, 184.43mg potassium (mg/100gm) and 0.912mg vitamin C in 100 ml. The prepared beverage was stored for 30 days under refrigerated and normal conditions, and changes in TSS, pH and acidity were observed: 12.413.3%, 5.72-5.214, 0.32-0.43%, and 12.4-13.8%, 5.72-4.64, 0.32-0.68% respectively. Overall analysis showed that the beverage prepared with 85% liquid whey and 15% banana juice could be stored for 30 days under refrigerated conditions without the addition of preservatives.